Evaluation of Treatment Outcomes and Quality of Life in Patients with Obstructive Sleep Apnea Receiving Oral Appliance Therapy - T Anjan; Smit Thakkar; Abhishek Jahagirdar; Harshitha Baddam; Swati Manohar Pappulwar; Kunal Jha; M. C. Prashant (Journal of Pharmacy and Bioallied Sciences)
Background: A frequent sleep condition linked to considerable morbidity and death is obstructive sleep apnea (OSA). Continuous positive airway pressure (CPAP) therapy is not the only noninvasive treatment option for OSA. Another option is oral appliance therapy (OAT). The purpose of this study was to assess the quality of life and treatment results for OSA patients receiving OAT in a tertiary care environment. Methods: Over the course of 1 year, prospective observational research was carried out at a tertiary care facility. Patients with consecutive Obsructive Sleep apnea as per polysomnography report were enrolled in the sudy. Medical history, baseline demographics, and sleep characteristics were noted. Both before and after the start of OAT, objective sleep metrics and subjective results were evaluated. Adverse events and therapeutic compliance were tracked. To assess the effectiveness and tolerability of the medication, statistical analysis was done. Findings: The research had 150 patients in all, with a mean age of 52.4 years and a 66.7% male preponderance. Objective sleep metrics showed considerable improvements after starting OAT, with the apnea-hypopnea index decreasing from 28.7 to 9.3 episodes per hour (P < 0.001). Improvement was also evident in subjective outcomes as ESS ratings dropped from 12.6 to 6.2 (P < 0.05). Evaluations of quality of life indicated improvements in the categories of physical and mental health (P < 0.001). There were few reported adverse effects and a good level of adherence to OAT. In tertiary care settings, OAT is an effective and well-tolerated therapeutic option for individuals with OSA. The noteworthy enhancements in treatment results and overall well-being highlight the practicality of OAT as a substitute for CPAP therapy. To fully understand the long-term effectiveness and cardiovascular advantages of OAT in the treatment of OSA, more investigation is necessary.